2017
DOI: 10.1002/jmv.24864
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine response in crimean‐congo hemorrhagic fever virus infection

Abstract: We described the predictive role of cytokines in fatality of Crimean Congo Hemorrhagic Fever Virus (CCHFV) infection by using daily clinical sera samples. Consequent serum samples of the selected patients in different severity groups and healthy controls were examined by using human cytokine 17-plex assay. We included 12 (23%) mild, 30 (58%) moderate, 10 (19%) severe patients, and 10 healthy volunteers. The mean age of the patients was 52 (sd 15), 52% were female. Forty-six patients (88%) received ribavirin. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 20 publications
5
43
0
2
Order By: Relevance
“…Despite the known challenges in drawing comparisons, we observed several parallels between the responses we recorded in Ifnar -/mice and reports of severe human disease. Ifnar -/mice demonstrated increased levels of proinflammatory cytokines (IL-1β, IL-6, CXCL10, TNF-α), and the anti-inflammatory cytokine IL-10, all of which have been associated with fatal outcomes in humans [50][51][52]. Increased levels of murine CXCL1 and CXCL2, functional homologs of human IL-8, correlate with reports of IL-8 as a diagnostic marker for disease severity in humans [52].…”
Section: Differential Cytokine Expression In Mice Infected With Eithementioning
confidence: 85%
See 1 more Smart Citation
“…Despite the known challenges in drawing comparisons, we observed several parallels between the responses we recorded in Ifnar -/mice and reports of severe human disease. Ifnar -/mice demonstrated increased levels of proinflammatory cytokines (IL-1β, IL-6, CXCL10, TNF-α), and the anti-inflammatory cytokine IL-10, all of which have been associated with fatal outcomes in humans [50][51][52]. Increased levels of murine CXCL1 and CXCL2, functional homologs of human IL-8, correlate with reports of IL-8 as a diagnostic marker for disease severity in humans [52].…”
Section: Differential Cytokine Expression In Mice Infected With Eithementioning
confidence: 85%
“…Ifnar -/mice demonstrated increased levels of proinflammatory cytokines (IL-1β, IL-6, CXCL10, TNF-α), and the anti-inflammatory cytokine IL-10, all of which have been associated with fatal outcomes in humans [50][51][52]. Increased levels of murine CXCL1 and CXCL2, functional homologs of human IL-8, correlate with reports of IL-8 as a diagnostic marker for disease severity in humans [52]. Finally, changes in clinical chemistry and CBC values reported in humans as important diagnostic markers for predicting disease severity, including elevated AST and ALT, elevated neutrophils, and lymphopenia [1,17,53,54], were also seen in Ifnar -/mice as disease severity increased.…”
Section: Differential Cytokine Expression In Mice Infected With Eithementioning
confidence: 99%
“…IFN‐γ was similar between both groups (Kaya et al., ). A more recent student study similarly showed increased IL‐6 and TNF‐α in fatal cases ( n = 5) compared with non‐fatal cases ( n = 22), with IL‐8 being an additional marker for fatality (Ergönül et al., ).…”
Section: Future: Advances In Animal Models and Therapeutics For Cchfvmentioning
confidence: 93%
“…The patients were divided into those with mild-moderate disease and those with severe disease according to the criteria defined by Swanepoel et al and the modified criteria recommended by Ergönül et al [7,8], as well as the clinical indicators of poor prognosis. Forty patients were included in the mild-moderate group, 16 patients in the severe group, and 4 patients in the fatal group.…”
Section: Study Groupsmentioning
confidence: 99%